The impact of Ethiopia’s Productive Safety Net Programme on the nutritional status of children: 2008–2012 - Berhane, Guush; Hoddinott, John F.; Kumar, Neha (International Food Policy Research Institute, 2017)
Ethiopia’s Productive Safety Net Programme (PSNP) is a large-scale social protection intervention aimed at improving food security and stabilizing asset levels. The PSNP contains a mix of public works employment and unconditional cash and food transfers. It is a well-targeted program; however, several years passed before payment levels reached the intended amounts. The PSNP has been successful in improving household food security. However, children’s nutritional status in the localities where the PSNP operates is poor, with 48 percent of children stunted in 2012. This leads to the question of whether the PSNP could improve child nutrition. In this paper, we examine the impact of the PSNP on children’s nutritional status over the period 2008–2012. Doing so requires paying particular attention to the targeting of the PSNP and how payment levels have evolved over time. Using inverse-probability-weighted regression-adjustment estimators, we find no evidence that the PSNP reduces either chronic undernutrition (height-for-age z-scores, stunting) or acute undernutrition (weight-for-height z-scores, wasting). While we cannot definitively identify the reason for this non-result, we note that child diet quality is poor. We find no evidence that the PSNP improves child consumption of pulses, oils, fruits, vegetables, dairy products, or animal-source proteins. Most mothers have not had contact with health extension workers nor have they received information on good feeding practices. Water practices, as captured by the likelihood that mothers boil drinking water, are poor. These findings, along with work by other researchers, have informed revisions to the PSNP. Future research will assess whether these revisions have led to improvements in the diets and anthropometric status of preschool children in Ethiopia.